Teaching and learning in higher education : disciplinary approaches to educational enquiry - Cleaver, Elizabeth; Lintern , Maxine ;McLinden, Mike (Los Angeles, California : Sage, 2014)
In today's higher education climate, academic staff are encouraged to focus not only on the up-to-date content of their teaching, but also to identify the most effective ways to engage students in learning, often alongside other key transferrable skills. This had led to a growing requirement for staff to adopt a scholarly approach to learning and teaching practice, and to undertake scholarship of learning and teaching as part of ongoing professional development. This text explores broad best practice approaches to undertaking enquiry into learning and teaching in higher education. It provides an accessible introduction for staff who have been educated within a range of academic disciplines, often with high-level but very focused knowledge about, and understandings of, research processes to the potentially new world of educational enquiry. This is complemented by chapters exploring what educational enquiry means in the context of different academic disciplines.
Part One. Understanding Educational Enquiry -- 1. What is educational enquiry and why is it important? -- 2. What do I need to know before I read educational literature? -- 3. How is educational literature evidenced and reviewed? -- 4. What about ethics and safety? -- 5. What kind of data should I collect and use? -- 6. What about dissemination? / Elizabeth Cleaver -- Part Two. Enquiry in the Disciplines -- 7. Enquiry into learning and teaching in the physical sciences -- 8. Enquiry into learning and teaching in mathematics and engineering -- 9. Enquiry into learning and teaching in the life sciences -- 10. Enquiry into learning and teaching in arts and creative practice -- 11. Enquiry into learning and teaching in the humanities -- 12. Enquiry into learning and teaching in the health professions -- 13. Enquiry into learning and teaching in the professions: the case of law.
Includes bibliographical references and index.
Keywords: COLLEGE TEACHING